Human Capital or Discrimination: Addressing Income, Employment, and Wealth Gaps Between Black and White Americans - Vuojärvi, Aava (My University, 2024)
This master thesis examines what factors have contributed to the gap in income, employment, and wealth between White and Black Americans. The study reviews the literature on the Black-White gaps in human capital accumulation and the evolution of discrimination models from the late 1950s to the 21stc century. It then investigates racial disparities within institutional frameworks, providing examples from financial, governmental, and health institutions as they show potential for structural racial bias. Lastly, the study explores the effectiveness of minimum wages, credit market expansion, and education design as examples of policies to reduce discrimination and human capital accumulation differences as well as the potential of algorithmic decision-making to reduce racial bias in economic outcomes.
Keywords: economic inequality, United States, race, discrimination, human capital, institutions